Design of a fault-tolerant Ethernet-based networked control system with zero-packet loss for critical time applications - Soliman, Khalid (AUC Knowledge Fountain, 2019)
The use of Ethernet as a communication protocol for Networked Control Systems (NCS) is gaining interest in the automation community. The applications of such protocols range from industrial control to automotive and aerospace. The demand for using new architectures to guarantee system tolerance to faults and failures of single or multiple nodes is increasing. This is because such a system design decreases production downtime, thereby increasing system profitability. An NCS Fault-Tolerant system model is proposed and simulated in this study for critical time applications such as pharmaceutical manufacturing processes. The simulation results show that the introduced architecture functions appropriately and can accommodate the failure of more than one controller node in the production scheme. In addition to focusing on the NCS design aspects, this thesis includes a reliability and finance study. A Markov chain model is introduced to estimate the steady-state availability for the proposed NCS. Hence, the present research offers different optimized controller boards inventory strategies along with a cost analysis designed to increase both productivity and profitability.